AB0472 Ocular Toxicity of Hydroxychloroquine is More Frequent in Male Patients. (10th June 2014) - Helvaci, O.; Sancioglu, H.; Karadag, O.; Kilic, L.; Akdogan, A.; Bilgen, S.; Ertenli, I.; Kiraz, S.; Kalyoncu, U.
Abstract : Background: Hydroxychloroquine (HQ) is widely used to treat for rheumatoid arthritis and connectice tissue disorders. Due to the potential of ocular toxicity, routine ophtalmological assessment (ROA) is essential for sight safety. Objectives: The objective of this study was to evaluate the reasons to cease HQ. Second objective was to assess frequency of ocular toxicity and associated risk factors during HQ treatment. Methods: In our outpatient clinic, patients with rheumatoid arthritis (RA) and connective tissue disorders such as systemic lupus erythematosus (SLE), Sjogren's syndrome (SS) and overlap were assessed consecutively for status of HQ by a standard questionnaire between December 2013 and January 2014. Patients who used HQ less than 1 year (13.6%) were excluded from study. Only if ophthalmologist advised to cease HQ due to ocular toxicity, we accepted phenomenon as a ocular side effect. However two patients' ophthalmologic examination were not found in their charts, so they were accepted to ceased the drugs themselves. Patients with ocular toxicity were not reevaluated by an ophthalmologist. Cumulative HQ dosage and risk factors for ocular toxicity were assessed by using Mann-Whitney U test. Results: A total of 266 patients (90.6% female) were enrolled. Mean age was 50±13.5 years, and median disease duration was 8 years (1-50). Underlying diseases were RA [148 (56%)], SLE [63 (24%)], SS [31 (12%)], overlap and others [24 (9%)]. Median duration of HQ treatment was 6 years (1-28) and median dose was 400 mg/day (min 200-max 400 mg/day). In 46 (17.3%) patients HQ was ceased. The reasons were ocular toxicity 22 (47.8%), patient non-adherence 9 (19.6%), dermatological side effect 3 (6.5%), others 12 (26.1%). Twenty two of all 266 (%8.3) patients developed ocular toxicity. Ocular toxicity was similar for all diseases. Ocular toxicity was demonstrated by an ophthalmologist in 20 patients, the other two patients had blurry vision so they ceased HQ themselves. Ocular toxicity was more frequent in males (5/20 (20%) vs 17/241 (7%), p=0.025). Median cumulative HQ dosage in patients with ocular toxicity was 864 gram (108-2160) in other words 12.9 gr per kilogram (1.2-40). Older age (58±10 vs 50±13, p=0.008), longer disease duration (14.8±11.5 vs 9.2±7.1 years, p=0.013), and longer HQ duration (10±6.3 vs 7.1±5.6 years, p=0.023) were associated with ocular toxicity. Conclusions: Among regularly follow-up patients, ocular toxicity of HQ was not rare in a rheumatology outpatient clinic. Cumulative dose for ocular toxicity was 13 gram/kilogram; however, certain patients developed toxicity with 1 gram/kg/day. Although, our cohort was predominantly female, ocular toxicity was seen more frequently in male patients. Other known risk factors such as longer disease duration, longer HQ usage and older age were also demonstrated in our patients. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5352